Peran Ultrasonografi (US) dalam Pemeriksaan Post-Mortem: Sebuah Studi Literatur - Yen, Liauw Djai; Saputro, Alexandra Ambar; Suwito, Michelle Margaretha; Damanik, Eunike Marshya Easter; Hadiwinata, Evellyn; Anastasia, Cindy; Sinurat, Radinka Genevieve Theopilia (Jurnal Kedokteran Meditek, 2026)
Introduction: The global decline in autopsy rates has raised concerns about its consequences for education and research. Virtual autopsy offers a non-invasive alternative to conventional procedures, avoiding tissue destruction and gaining wider family acceptance. Ultrasonography (US) is widely available, relatively inexpensive, and has emerging potential in post-mortem evaluation. Purpose: To review the role of US as a post-mortem imaging modality as an alternative method to conventional autopsy. Methods: A literature search was conducted in PubMed, Google Scholar, and the Journal of Forensic Sciences for studies published between 2019 and 2025. Eligible designs included prospective diagnostic studies, case reports, systematic reviews, and descriptive observational research. Reported statistical analyses involved sensitivity and specificity calculations, logistic regression, diagnostic accuracy meta-analyses, and Fisher’s exact test (p<0.05). Results: With the advancement of technology, virtual autopsy can provide important information that helps determine the cause and manner of death. Early post-mortem US has been shown to identify aortic dissection, pericardial and pleural effusions, pneumothorax, deep vein thrombosis (DVT), and pulmonary embolism. In forensic practice, US is used as a complementary technique, reducing the need for extensive autopsy exploration and limiting biological exposure risks to forensic staff. Conclusion: Post-mortem US is a practical and effective tool for detecting pathological findings, particularly in resource-limited settings or when infection risk is high. However, its diagnostic performance is constrained by gas artifacts, tissue cooling, and limited access to internal organs. Further research is needed to standardize techniques and validate diagnostic accuracy.